Repercussions of Zika virus emergency in the health of the population of Tocantins, Brazil, 2015 and 2016: a descriptive study - Rodrigues, Meire da Silva Pereira (2020)
Objective. To describe the occurrence of Zika and its complications in the state of Tocantins and in its capital, the city of Palmas. Methods. Descriptive study using data from Official Information Systems. Results. The incidence of reported cases of Zika in 2015 and 2016 was 295.2/100,000 and 411.1/100,000 inhabitants, respectively and 5.9/1000 and 27.8/1000 NV in pregnant women. Higher risks occurred in women, age 20-39 years, municipalities in the central and northwestern regions and hotter months (February and March). The incidence of Zika-related microcephaly at pregnancy was 0.06/1000 NV. One case of Guillain Barré Syndrome resulting from Zika virus infection has been confirmed. Conclusion. Zika virus fever has hit Tocantins intensely. However, their adverse outcomes have been less frequent than in others states.